Human resource practices, organisational commitment and turnover intention among bank employees in Sarawak, Malaysia - Mark, Kasa; Sherrymina, Kichin; Zaiton, Hassan; Sheena, Poh; Nursyafiqah, Ramli (Asian Academy of Management (AAM) and Penerbit Universiti Sains Malaysia, 2023)
Banking industry is becoming more competitive due to escalating bank branches every year. It has been recorded that one of the industries with highest rate of turnover is financial service sector. Employee turnover is contributed by demanding working atmosphere and burdensome workloads. High turnover rate can adversely influence bank’s performance and productivity. It has been exhibited in previous studies concerning association between human resource practices and turnover intention and the role of organisational commitment as a mediator between human resource practices and turnover intention. A total of 283 questionnaires were distributed to bank employees in Kuching, Sarawak, Malaysia. Data analysis disclosed that there is a negative relationship between human resource practices and turnover intention and organisational commitment mediates the associations. The results of the study revealed the importance of bank employers to improve its current human resource practices for boosting organisational commitment and lowering employee turnover intention. Originality/value of this research study lies on its contribution as the first field study to be performed in Sarawak, Malaysia in relations to human resource practices on turnover intention among bank employees with mediating role of organisational commitment.